Electrochemical and Tribological Behavior of Dual-Phase Steels Obtained from a Commercial-Grade API 5CT Steel - C. Guerra-Linares; M. J. Soria-Aguilar; J. García-Guerra; A. Martínez-Luevanos; F. R. Carrillo-Pedroza; E. Gutíerrez-Castañeda; J. C. Díaz-Guillén; J. L. Acevedo Dávila; J. M. González de la Cruz (Metals)
In this study, the effect of martensite volume fraction on the mechanical, tribological, and corrosion properties of API 5CT dual-phase steel is studied based on intercritical heat treatment routes at different temperatures (730, 760, and 790 °C). Hardness of the specimens increased by increasing the martensite volume fraction up to 50%. Further increase in martensite volume fraction led to an increase in wear resistance. Sliding wear pin-on-disk tests were analyzed following the ASTM G99 standard, obtaining the wear rate, the volume of lost mass, and the Archard coefficient as a function of time and temperature of the heat treatment. A comparison was made between the wear rate and the hardness data, and its proportionality was established. The corrosion behavior of DP steels in 3.5% NaCl solution was studied by the potentiodynamic polarization technique. The result showed that with increasing the martensite amount in the specimen and decreasing the ferrite amount, the corrosion rate decreased. Finally, the corrosion mechanism in DP steel depends on the self-corrosion resistance behavior of both phases (martensite-ferrite) as well as the presence of galvanic corrosion between them.